Improvement of semen quality in Longyou Partridge Chicken by dietary N-acetyl-L-glutamic acid and its mechanism study - Xue Du; Xiaopeng Tong; Xintong Qian; Yuanning Zhang; Duoxi Li; Xiaojun Liu; Xianzhong Zheng; Ayong Zhao (Poultry Science, 2025)
The aim of the study was to investigate the mechanisms of the N-acetyl-L-glutamic (NAG) diet in improving rooster semen quality after cryopreservation. A total of 60 individually housed chickens were randomly allocated to three groups: a basal diet group (C), a basal diet supplemented with 2 g/kg NAG group (NL), and a basal diet supplemented with 4 g/kg NAG group (NH). Semen quality was evaluated on days 15 and 30, including fresh sperm motility and cryopreservation efficacy. Serum biochemical parameters, hormone levels, immune indices, semen metabolites, and gut microbiota composition were assessed at 30 d. NAG supplementation significantly improved semen quality. At 15 and 30 d, both NL and NH groups showed a significant increase in the total motile sperm ratio (TM) in fresh semen compared to the control (P ≤ 0.05). At 30 d, group NH exhibited significantly higher percentage of sperm in a straight-line trajectory (LIN) in fresh semen than both the C and NL groups. After cryopreservation, the sperm TM and LIN from chickens with NAG dietary for 30 days were significantly better in the NL group compared to C and NH groups (P ≤ 0.05). Metabolomic analysis identified significant upregulation of metabolites, including melatonin and ferulic acid, in cryopreserved semen from NAG-supplemented groups, while 5-hydroxylysine and inosine-1-phosphate were significantly reduced. Serum antioxidant capacity, as measured by glutathione peroxidase (GSH-Px) was significantly higher, while malondialdehyde (MDA) levels lower in NAG groups compared to C (P ≤ 0.05). No significant differences in immune markers or reproductive hormones were observed across groups. Gut microbiota analysis revealed that NAG supplementation enhanced beneficial bacterial populations. In conclusion, NAG supplementation improved sperm motility and cryopreservation outcomes, potentially by increasing the levels of semen melatonin and ferulic acid and reducing the body oxidative stress. And it can improve the overall health level by regulating the gut microbiota through diet. These findings highlight NAG’s potential as a dietary supplement to improve semen quality and overall reproductive efficiency in poultry.